Comparison of the Rermineralisation Effect of a Glass Ionomer Cement Versus a Resin Composite on Dentin of Primary Teeth - Aykut-Yetkiner, A.; Şimşek, Deniz; Simsek, D.; Çiftçioğlu, Muhsin; Eronat, C.; Ciftcioglu, M. (Ariesdue Srl, 2014)
Aim The aim of this study was to investigate the interaction of a high viscosity glass ionomer cement (G/C) and a composite resin with caries affected dentin and to determine the remineralization levels. Materials and Methods In a split Mouth deSign 24 GIC and composite resin atraumatic restorative treatment restorations were made in vivo and the teeth were collected after 2 years and subsequently settioned and examined using Vickers microhardness test; the latter was performed starting from the dentin surfate adjacent to the restoration. Repeated Measure ANOVA and Bonferroni Statistical methods were used for data analysis. Results The micrdhardness adjacent to the GIC reStorative material resulted tube significantly higher. Conclusion GIC resulted to be a better restorative material for the remineralization of caries affected dentin, though further studies are necessary for the corroboration of this finding. The GIC restored primary molar dentin had a higher level of remineralizatiOn and GIC could be the material of chdice in pediatric dentistry.
Keywords: Atraumatic Restorative Treatment; Composite; Glass Ionomer Cement; Microhardness; Remineralization